Visualizing technocratic power: a cyber-archaeological analysis of the US National Education Technology Plan. Issue 2 (4th March 2021) - Wiebe, Chris; Nguyen, Ai-Khanh; Mattheis, Allison
ABSTRACT: Situated in an understanding of contemporary US education as heavily influenced by a neoliberal technocracy we conducted a Critical Discourse Analysis of the 2010 and 2016 National Education Technology (NETP) plans released by the US Department of Education. Our investigation was also guided by a cyber-archaeological excavation of digital artifacts that traced the influence of data analytics companies on the development of educational policy. Expressive values emerged prominently as a discourse feature that functions in the NETP document to formulate a tech-invigorated reality. Our examination of the NETP documents revealed three primary themes: (1) the promotion of marketization processes in education as a signifier of progress; (2) the construction of an idealized android learner; and (3) ubiquitous digital access as equitable opportunity to learn. We conclude that the NETP serves to promote a particular educational agenda that benefits corporate and private interests.